Analisis Dampak Jika Redenominasi Dilakukan: Pengaruhnya terhadap Daya Beli Masyarakat Indonesia - Kartika Dewi (Bina Nusantara University, 2013)
The government of Indonesia has approved Bank Indonesia to redenominated Rupiah currency by eliminating three zeros starting 2011 until 2020. The Law itself is still waiting an approval from Right and Human Right Ministry then passed by the House of Representatives. The problem occurs when RupiahRedenomination will make purchasing power lower for most Indonesia. There are many pros and contras about this plan. Opponents claimed it will make the economy worse. On the other hand, Proponents can wait to see Rupiah will have the same value with other currencies, boost up rupiah credibility in international. Writer wants to analyze this plan from purchasing power for Indonesian when the program will be implemented this year 2013. Of course, it will have positive side as well as negative side. The fact that the prices for goods and servicesalways increase each month and those increases will accumulated at the end of the year will result significant increase. This big increase will result big inflation. The truth is inflation is rising up in Indonesia everyday. Government told inflation is under control but most Indonesian is getting suffered with this price increase. Most people can not afford for basic necessities. Businessmen tried to increase their employess salaries and wages but the increase is smaller than its goods pricess in results the increase in salary and wage can not cover the prices hike for goods. Journal is made by collecting information through internet, simple questioners with students and employes with Binus University campus,text-books, own experiences as Indonesian citizen.Then writer drawn a conclusion and suggestions. The result from this research based on simple questioner is disagreement on Rupiah Redenomination. At the end, writer concludes that Indonesia needs good moral citizens who can make a drastic change for Indonesian’ sake.